Legal Framework for Human Rights Protection in Africa - Garayová, Lilla (Regional Human Rights Protection Systems Outside Europe, 2026)
This chapter examines the development and framework of the African regional human rights system, emphasising its evolution within the broader context of international human rights law. Following World War II, regional human rights systems emerged alongside the United Nations’ (UN) efforts, with Africa establishing a distinct framework in response to global standards and regional needs.The study explores how the youngest regional system of human rights protection evolved, what influenced the creation of instruments, such as the African Charter on Human and Peoples’ Rights, the African Charter on the Rights and Welfare of the Child, and protocols addressing specific issues, including women’s rights, disability rights and the rights of older persons. Additionally, the study addresses the roles of key African human rights institutions, including the African Commission and African Court on Human and Peoples’ Rights. Keywords: African human rights system, African Charter on Human and Peoples’ Rights, African Commission on Human and Peoples’ Rights, African Court on Human and Peoples’ Rights, regional human rights instruments, African Union, Maputo Protocol, Kampala Convention, African Charter on the Rights and Welfare of the Child, human rights institutions in Africa